Stopping rules for majority voting : A public choice experiment - Dougherty, Keith L.; Kisaalita, Alice; McKissick, Jordan; Katz, Evan (My University, 2020)
Some solution concepts make the same equilibrium prediction regardless of how voting ends. As a result, experimentalists have used a variety of stopping rules without carefully considering the consequences. This experiment compares majority decision making in committees using one of three stopping rules: vote by a majority to adjourn, a fixed time period, and the chair decides when to adjourn. We compare these rules for groups of five subjects using two distributions of ideal points studied by Fiorina and Plott (1978). Although we find few differences between voting to adjourn and ending after a fixed time period, we find noticeable differences between groups with the chair decides to adjourn and those without. Allowing the chair to determine adjournment produces outcomes more favorable to the chair and can make the voting process continue for more than three times as many rounds as the other two treatments. Such results should help committees improve the rules governing their decisions.